2020
DOI: 10.1038/s41419-020-03189-z
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and breast cancer drug resistance

Abstract: Drug resistance is a daunting challenge in the treatment of breast cancer (BC). Exosomes, as intercellular communicative vectors in the tumor microenvironment, play an important role in BC progression. With the in-depth understanding of tumor heterogeneity, an emerging role of exosomes in drug resistance has attracted extensive attention. The functional proteins or non-coding RNAs contained in exosomes secreted from tumor and stromal cells mediate drug resistance by regulating drug efflux and metabolism, pro-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
97
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 127 publications
1
97
0
1
Order By: Relevance
“…EMT has been associated with cancer stemness, characterized by an increase in the number of cancer stem cells (CSCs) (13)(14)(15)(16). CSCs are subclone cells in the tumor tissue that obtain stem cell traits (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…EMT has been associated with cancer stemness, characterized by an increase in the number of cancer stem cells (CSCs) (13)(14)(15)(16). CSCs are subclone cells in the tumor tissue that obtain stem cell traits (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…[13,17]. It has been demonstrated that EVs are involved in resistance mechanisms [32] and may induce immune escape by releasing proapoptotic molecules [33]. Another study by Federici et al has also illustrated that low pH-induced reduction of antitumor drug uptake and increased release of EVs with an antitumor drug are important mechanisms for the occurrence of drug resistance [34].…”
Section: An Overview Of Extracellular Vesiclesmentioning
confidence: 99%
“…Breast tumor-derived EVs have been reported to have a role in all cancer hallmarks controlling a wide range of pathways and regulating gene expression by transferring their intra-vesicular content (proteins, lipids, enzymes, metabolites, DNA, mRNA, miRNA, long and short non-coding RNA) into recipient cells [ 40 ]. In addition to regulating invasion, vessel formation, pre-metastatic niche preparation, and immune surveillance escape, the bioactive molecules carried by EVs have been proposed as important players in the mechanisms of resistance to therapeutic treatments [ 41 , 42 ] and might represent promising candidate biomarkers for breast cancers [ 43 , 44 ].…”
Section: Overview Of Extracellular Vesiclesmentioning
confidence: 99%